2010
DOI: 10.3109/09513590.2010.501875
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing hormone therapy for future reproductive performance in women with premature ovarian failure

Abstract: With increasing success in treatment of childhood cancer there is a growing population of women with premature ovarian failure (POF) seeking fertility treatment. Various preparations of estrogen and progestogen are prescribed for young women with POF. While the dose and duration of hormone therapy (HT) is usually adjusted according to the patient's height and the Tanner's stage of development for young pre-pubertal women, the optimal effective HT regimen to maximise the reproductive potential for young as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
0
8
1
Order By: Relevance
“…To our knowledge, no cases of hemangioma related to the antineoplastic treatment have been reported in literature whereas they are typically reported in female young adults with history of oral contraceptive therapy (12). The use of oral contraceptives is indicated in the treatment of young women with premature ovarian failure caused by antineoplastic treatment (14,15). Maybe our findings have to be interpreted considering that all of the patients with hemangiomas were girls with a median age of 18.3 years, half of which were receiving oral contraceptive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no cases of hemangioma related to the antineoplastic treatment have been reported in literature whereas they are typically reported in female young adults with history of oral contraceptive therapy (12). The use of oral contraceptives is indicated in the treatment of young women with premature ovarian failure caused by antineoplastic treatment (14,15). Maybe our findings have to be interpreted considering that all of the patients with hemangiomas were girls with a median age of 18.3 years, half of which were receiving oral contraceptive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also implicated the involvement of the mTOR pathway in the development of leiomyomas. Makker et al, (36) showed that mTOR signaling is increased in leiomyomas, while Yin et al (37), revealed that estrogen requires mTOR to drive G1 cell cycle progression in leiomyomas. Elongation factor 2 (EF2), a gene that functions in protein synthesis and a downstream mediator of the mTOR pathway, is involved in control of global translation.…”
Section: Discussionmentioning
confidence: 99%
“…HRT currently represent the mainstay therapy for women with POI and plays a pivotal role in reducing long-term comorbidities (e.g. osteoporosis and cardiovascular disease) and improving sexual health by restoring normal serum estrogen concentrations according to age (3,8,31).…”
Section: Discussionmentioning
confidence: 99%